2002
DOI: 10.1046/j.1523-1747.2002.01861.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonists of Peroxisome Proliferator-Activated Receptor γ Inhibit Cell Growth in Malignant Melanoma

Abstract: Peroxisome proliferator-activated receptor gamma is a member of the nuclear receptor superfamily involved in adipocyte differentiation and glucose homeostasis. There is evidence that peroxisome proliferator-activated receptor gamma may also act as a tumor suppressor. Here, we demonstrate expression of peroxisome proliferator-activated receptor gamma in benign melanocytic naevi, different variants of primary cutaneous melanomas, and melanoma metastases. Peroxisome proliferator-activated receptor gamma protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 28 publications
7
65
0
Order By: Relevance
“…In addition to nonmelanoma skin cancer, there have been reports of a possible role of PPARs in malignant melanoma (i.e., PPARg activation was reported to inhibit the proliferation of human melanoma and melanocyte cell lines) (38,109). A recent report, however, evaluating the putative risk of genetic polymorphisms in the PPARg gene for the development of malignant mela- noma has yielded inconsistent results in two independent case-control studies (110).…”
Section: Role Of Ppar In Skin Cancermentioning
confidence: 99%
“…In addition to nonmelanoma skin cancer, there have been reports of a possible role of PPARs in malignant melanoma (i.e., PPARg activation was reported to inhibit the proliferation of human melanoma and melanocyte cell lines) (38,109). A recent report, however, evaluating the putative risk of genetic polymorphisms in the PPARg gene for the development of malignant mela- noma has yielded inconsistent results in two independent case-control studies (110).…”
Section: Role Of Ppar In Skin Cancermentioning
confidence: 99%
“…The antitumorigenic effects of PPARg ligands have been well documented (Yang and Frucht, 2001;Haydon et al, 2002;Mossner et al, 2002;Osawa et al, 2003). Numerous studies have demonstrated that troglitazone (TRO), a synthetic PPARg ligand, causes growth inhibition, induces differentiation, and triggers apoptosis of various human malignant cells (Asou et al, 1999;Clay et al, 1999;Demetri et al, 1999;Sugimura et al, 1999;Hisatake et al, 2000;Rumi et al, 2001;Takashima et al, 2001;Begum et al, 2002;Yoshizawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma cells, these antiproliferative effects of PPAR-c agonists were also reported [14,15,17]. The PPAR-c specific ligands 15-d-PGJ2, troglitazone, and rosiglitazone dose-dependently inhibited proliferation of melanoma cells at concentrations between 0 and 50 lM [14].…”
Section: Ppar-c Activators Inhibit Cell Growth In Human Melanocytesmentioning
confidence: 81%
“…The PPAR-c specific ligands 15-d-PGJ2, troglitazone, and rosiglitazone dose-dependently inhibited proliferation of melanoma cells at concentrations between 0 and 50 lM [14]. Ciglitazone and PGJ2 not only inhibited A375 and WM35 melanoma cell proliferation but also induced apoptosis [17].…”
Section: Ppar-c Activators Inhibit Cell Growth In Human Melanocytesmentioning
confidence: 98%